2014
DOI: 10.1007/s11904-014-0236-6
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Methods and Risk of HIV Acquisition or Female-to-Male Transmission

Abstract: Effective family planning with modern contraception is an important intervention to prevent unintended pregnancies which also provides personal, familial, and societal benefits. Contraception is also the most cost-effective strategy to reduce the burden of mother-to-child HIV transmission for women living with HIV who wish to prevent pregnancy. There are concerns, however, that certain contraceptive methods, in particular the injectable contraceptive depot medroxyprogesterone acetate (DMPA), may increase a wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 132 publications
(148 reference statements)
2
22
0
1
Order By: Relevance
“…Some studies indicate no link between contraceptive use and risk of HIV-1 (Heffron et al 2013, whereas others reported significant risk with contraceptive use (Heffron et al 2012, Haddad et al 2014. Recently, by examining individual participant data instead of an aggregate of different studies, an increase in risk was found to be associated with the use of P 4 -containing contraceptives (Morrison et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate no link between contraceptive use and risk of HIV-1 (Heffron et al 2013, whereas others reported significant risk with contraceptive use (Heffron et al 2012, Haddad et al 2014. Recently, by examining individual participant data instead of an aggregate of different studies, an increase in risk was found to be associated with the use of P 4 -containing contraceptives (Morrison et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The use of injectable hormonal contraceptives in women increased from 4.5% in 1995 to 23% in 2006 to 2010 (28). A number of studies have suggested an increased risk of acquisition of HIV in association with DMPA (29)(30)(31). It is of interest that one of the highest reported rates of HSV-1 genital herpes was detected in participants of the Herpevac trial study, all of which were required to use a highly effective method of birth control that included hormonal contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Recently, much attention has been given to the impact of hormonal contraception on HIV disease progression and HIV transmission and acquisition, though evidence of the impact on transmission and acquisition remains inconclusive. [15][16][17][18][19] There have been many calls for integrated family planning and HIV programming efforts; however, evidence of effective integration models have lagged behind and are only slowly emerging. 20,21 The legal status of abortion in many countries and pervasive stigma have also resulted in less information on the relationship between HIV and abortion, including the safety of abortion in the context of HIV and access to post-abortion care.…”
Section: Resultsmentioning
confidence: 99%